Technical keys in maximizing finger proximal interphalangeal joint motion after vascularized toe joint transfers. (September 2019) - Lin, Yu-Te
Vascularized toe joint transfers to the fingers have been performed for more than four decades, but their outcomes are not comparable with implant arthroplasty. Limited range of motion and extensor deficits of about 30° remain major problems with the constructed joints. We observed that the central extensor tendon of the toe is often attenuated proximally in its course on the dorsum of the proximal interphalangeal joint. A tight repair of the toe extensors to finger extensors limits joint motion. We reviewed our surgical techniques with this consideration. Thirty-eight fingers that we followed for 6 to 123 months had active range of motion of the reconstructed proximal interphalangeal joint in the finger of 58° (range 17°–76°) with an extensor deficit of 18° (range 0°–30°). We consider that the extensor mechanism and central slip insertion to the middle phalanx must be reconstructed meticulously to improve joint motion and decrease extension lag, and design of a lateral skin flap paddle to better cover vessels and allow extensor repairs.